Decentralizing PrEP delivery: Implementation and dissemination strategies to increase PrEP uptake among MSM in Toronto, Canada. - Maxime Charest; Malika Sharma; Allison Chris; Alexandre Schnubb; David C Knox; James Wilton; Rita Shahin; Arlene Chan; Sharmistha Mishra; Daniel Grace; Ahmed M Bayoumi; John Maxwell; et al. (PLoS ONE)
Pre-exposure prophylaxis (PrEP) is traditionally prescribed by HIV specialist physicians. Given finite specialist resources, there is a need to scale up PrEP delivery by decentralizing services via other healthcare professionals. We aimed to assess the feasibility of delivering PrEP to men who have sex with men (MSM) through primary care physicians and sexual health clinic nurses. We piloted a multi-component, implementation and dissemination research program to increase provision of PrEP through primary care physicians and sexual health clinic nurses in Toronto, Canada. Community-based organizations (CBOs) provided prospective participants with information cards that contained links to an online module on engaging providers in a conversation about PrEP. In our patient-initiated continuing medical education (PICME) strategy, participants saw their family doctors and gave them the card, which also contained a link to a Continuing Medical Education module. In the nurse-led strategy, participants visited one of two participating clinics to obtain PrEP. We administered an optional online questionnaire to patients and providers at baseline and six months. CBOs distributed 3043 cards. At least 339 men accessed the online module and 196 completed baseline questionnaires. Most (55%) intended to visit nurses while 21% intended to consult their physicians. Among 45 men completing follow-up questionnaires at 6 months, 31% reported bringing cards to their physicians and obtaining PrEP through them; sexual health clinics delivered PrEP to 244 patients. Participants who went through the PICME approach reported no changes in relationships with their providers. Nurses showed fidelity to PrEP prescribing guidelines. Nurse-led PrEP and patient-initiated continuing medical education (PICME) for primary care physicians are feasible strategies to increase PrEP uptake. Nurse-led PrEP delivery was preferred by most patients.